Antioxidant and anti-inflammatory properties of the methanolic extract of Siphonochilus aethiopicus rhizomes - Elize Dadaya; Benoit Bargui Koubala; Herve Ngatanko Abaissou; Stéphane Zingue; Dieudonne Ndjonka (Shahrekord University of Medical Sciences, 2021)
Introduction: Siphonochilus aethiopicus is a medicinal plant widely used in the treatment of many inflammatory conditions such as arthritis. The objective of this study was therefore to evaluate the antioxidant and anti-inflammatory properties of methanolic extract of S. aethiopicus rhizomes. Methods: The total phenolic compounds, flavonoid, and tannin content, as well as the in vitro antioxidant activity of the extract, were estimated. The in vivo anti-inflammatory activity was then evaluated in male mice aged 3 to 4 months using the arthritic mouse model induced by carrageenan (0.05 ml; 1%) and monosodium urate (MSU) crystals (26.6 mg/mL). Mice were treated with the methanolic extract of S. aethiopicus (75, 150, 300 mg/kg) and the reference drugs: indomethacin (3 mg/kg) and colchicine (1 mg/kg). The serum, splenic, and hepatic lysosomal enzymes were determined, and oxidative stress biomarkers were estimated. Paws were sectioned for histological analysis. Results: Results showed that S. aethiopicus extract had non-negligible concentrations of polyphenols, flavonoids, and tannins, which could confer it an antioxidant effect. Further, the methanolic extract of S. aethiopicus at different doses significantly (P < 0.05) reduced paw swelling, attenuated joint inflammation, limited the release of lysosomal enzymes, and improved antioxidant enzymes. Conclusion: The methanolic extract of S. aethiopicus has anti-inflammatory and antioxidant properties, and can be used to treat acute forms of gouty arthritis.